ПОНЯТИЕ СПЕЦИАЛЬНЫХ ЗНАНИЙ И ВОЗМОЖНОСТИ ИХ ИСПОЛЬЗОВАНИЯ ПРИ РАССЛЕДОВАНИИ НЕЗАКОННОГО ОБРАЩЕНИЯ С ОРУЖИЕМ - Борисов, Станислав Геннадьевич (SUPREMANCE OF LAW, 2017)
The concept of “special knowledge”, which is used in the investigation of criminal offenses, is investigated. Based on the analysis of the opinions of forensic scientists, their own interpretation of this concept is provided. The main problematic issues related to the involvement of persons with special knowledge in the investigation of illicit use of weapons, ammunition or explosives are analyzed.
Keywords: criminal offense; criminal proceedings; special knowledge; specialist; expert; illicit use of weapons